REVIEWING THE DISCOURSE ON (POTENTIAL) "ENEMIES OF STANDARD ENGLISH" - Yazid Basthomi (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
This essay argues that Standard English is one among the varieties of English. Although speaking Standard English, as is the case with speaking other languages or varieties claimed to be the standard, might allow the speakers to gain particular privileges, it should not be readily surmised that this variety is more quality than the rest; difference does not necessarily mean difference in quality. As such, HoneyÃ¢â¬â¢s propagation that Standard English is more quality-thus warrants more attention-should be read on guard. This essay outlines whom Honey refers to as the enemies of Standard English. Subsequent to the outline, the essay presents points disclosing HoneyÃ¢â¬â¢s shaky argument. Critical presentation, against the backdrop of HoneyÃ¢â¬â¢s argumentation, of issues about nonnative speakers of English (if they are parties having the potential to corrupt English) will conclude the article.